2021
DOI: 10.1177/21501327211014065
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Barriers to Primary Care Services Utilization and its Associations with Overall Satisfaction of Patients in Saudi Arabia: A Cross-Sectional Questionnaire-Based Study

Abstract: Introduction: Primary care plays an integral role in modern healthcare systems. More so in a country that is currently undergoing a reform of its health system. Their remains barriers that hinder patients from seeking medical assistance from primary physicians. This study aims to examine the overall satisfaction of patients toward Primary Healthcare Centers (PHCs) in Saudi Arabia, as well as its association with potential barriers from a sample of patients who presented at the emergency department (ED) for non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…These 2 have been identified in other research as issues affecting patients' use of primary care and routine checkups in particular. 20,24,25 Mobile health clinics have been used to address geographic barriers (such as, no transportation) to health care. A mobile clinic tested in a rural region of the KSA was found overall to be very satisfying among the surveyed patients.…”
mentioning
confidence: 99%
“…These 2 have been identified in other research as issues affecting patients' use of primary care and routine checkups in particular. 20,24,25 Mobile health clinics have been used to address geographic barriers (such as, no transportation) to health care. A mobile clinic tested in a rural region of the KSA was found overall to be very satisfying among the surveyed patients.…”
mentioning
confidence: 99%
“…Barriers in the utilization of healthcare services, including bariatric services, are classified into different levels: organizational, care provider, and individual levels. Of all barriers, healthcare providers play a significant role in removing the obstacles to referring eligible patients for bariatric surgical management [31,32]. However, the current study found that more than half of the primary healthcare physicians had barriers in several categories.…”
Section: Discussionmentioning
confidence: 58%
“…15,16 Despite the continuous improvement and gradually increasing patients' satisfaction in PHCC services, 17 Saudis tend to visit EDs for healthcare services when they are sick, perceiving their condition to be serious. 18,19 Previous studies have reported that a high volume of non-urgent visits is attributed to pain, upper-respiratory tract infection/symptoms, and the renewal of medication prescriptions. 5,7 This study investigates non-urgent ED visits in our current local setting at an academic medical center.…”
Section: Introductionmentioning
confidence: 99%